Preliminary Exploration of Clinical Efficacy and Pharmacological Mechanism of Modified Danggui-Shaoyao San in the Treatment of Depression in Patients with Chronic Kidney Disease - Xia M; Ai N; Pang J (Dove Medical Press, 2022)
Mengdi Xia,1,2,* Na Ai,3,* Junjie Pang4 1Department of Nephrology, the Second Clinical Medical Institution of North, Sichuan Medical College (Nanchong Central Hospital), Nanchong, 637000, People's Republic of China; 2Department of Nephrology and Medical Intensive Care, Charite´-Universtitätsmedizin Berlin, Berlin, 12203, Germany; 3Department of General Internal Medicine, the Affiliated Traditional Chinese Medicine Hospital of Southwest Medical University, Luzhou, 646000, People's Republic of China; 4Hemodialysis Center, Santai County Traditional Chinese Medicine Hospital, Mianyang, 621100, People's Republic of China*These authors contributed equally to this workCorrespondence: Mengdi Xia; Junjie Pang, Email mengdix@163.com; junjiepang@yeah.netBackground: Depression in Chronic Kidney Disease (CKD) seriously affects the prognosis of patients and Modified Danggui-Shaoyao-San (MDSS) is based on the traditional Chinese formula Danggui-Shaoyao-San (DSS) for the treatment of depression, which is further optimized. The aim of this study was to evaluate the clinical efficacy and safety of MDSS for the treatment of depression in CKD, and to explain the molecular mechanism of MDSS for the treatment of depression in CKD through pharmacology and molecular docking.Methods: 62 patients were randomly divided into treatment group (treated with MDSS) and control group (treated with placebo) and assessed by Hamilton Depression Scale, and the primary outcome was to evaluate the efficacy of MDSS in improving depressive symptoms and the effect on liver and kidney function, electrolytes. In addition, we identified the core compounds and potential targets of MDSS through the TCMSP database. The GeneCards, OMIM and Disgenet databases were then used to identify molecular targets for CKD and depression. The target protein-protein interaction network was built using STRING database. Core targets were analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Molecular docking was used to verify the relationship between core active compounds and proteins.Results: Clinical results showed that CKD patients in the MDSS group had significantly improved depressive status with no significant adverse effects. By network pharmacology analysis, we found that the compound-target network mainly contained 47 compounds and 69 corresponding targets. 844 terms were analyzed by GO enrichment, and 254 signaling pathways in KEGG. Molecular docking showed that the top active compounds had high affinity with four targets.Conclusion: We preliminarily investigated the efficacy of MDSS in the treatment of depression in CKD and revealed the characteristics of multiple compounds and multiple targets in MDSS.Keywords: Modified Danggui-Shaoyao San, depression, chronic kidney disease, clinical efficacy, network pharmacology